2019
DOI: 10.3847/1538-4357/ab5110
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Broadband X-Ray Variability in the Dwarf Seyfert Galaxy NGC 4395

Abstract: We present a flux-resolved X-ray analysis of the dwarf Seyfert 1.8 galaxy NGC 4395, based on three archival XMM-Newton and one archival NuSTAR observations. The source is known to harbor a low mass black hole (∼ 10 4 − a few × 10 5 M ) and shows strong variability in the full X-ray range during these observations. We model the flux-resolved spectra of the source assuming three absorbing layers: neutral, mildly ionized, and highly ionized (N H ∼ 1.6×10 22 −3.4×10 23 cm −2 , ∼ 0.8−7.8×10 22 cm −2 , and 3.8×10 22… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…This effect has been confirmed in Type-2 AGN by Ricci et al (2014), and later confirmed in a large sample of CT sources by Boorman et al (2016). The fact that the slope of the R − L 2−10 correlation for NGC 4395 is consistent with unity is suggestive of a constant reprocessed flux despite the intrinsic variability (see Kammoun et al 2019b). This may indicate that despite the change in the LOS column density in this source, the overall covering fraction of the clouds remains constant.…”
Section: On the Obscurer Structurementioning
confidence: 65%
See 4 more Smart Citations
“…This effect has been confirmed in Type-2 AGN by Ricci et al (2014), and later confirmed in a large sample of CT sources by Boorman et al (2016). The fact that the slope of the R − L 2−10 correlation for NGC 4395 is consistent with unity is suggestive of a constant reprocessed flux despite the intrinsic variability (see Kammoun et al 2019b). This may indicate that despite the change in the LOS column density in this source, the overall covering fraction of the clouds remains constant.…”
Section: On the Obscurer Structurementioning
confidence: 65%
“…Such a configuration is not trivial to implement in the framework of the MYTorus models. A detailed analysis of NGC 4395 is presented in Kammoun et al (2019b) (see also Nardini & Risaliti 2011). As for NGC 3362, UGC 6100, and UGC 8621, the low quality of the data (for UGC 6100) makes the application of the MYTorus fits non-trivial.…”
Section: Mytorusmentioning
confidence: 99%
See 3 more Smart Citations